Вивчення елементного складу м’яти перцевої (Mentha piperita) - Андріанов, К. В.; Федченкова, Ю. А.; Хворост, О. П.; Андрианов, К. В.; Федченкова, Ю. А.; Хворост, О. П.; Andrianov, K. V.; Fedchenkova, Yu. A.; Khvorost, O. P. (Запорізький державний медичний університет, 2014)
Додаткового дослідження потребує доволі розповсюджена рослина – м’ята перцева (Mentha piperita) родини губоцвітих (Lamiaceae). У дикорослому стані невідома, є гібридом. Терапевтична активність рослини зумовлена комплексом біологічно активних речовин, серед яких є макро- та мікроелементи. З метою вивчення якісного складу та кількісного вмісту макро- та мікроелементів у листі дослідили три зразки м’яти перцевої за допомогою атомно-емісійної спектрометрії з фотографічною реєстрацією. Елементний склад усіх об’єктів, які вивчили, однаковий: 5 макро-,15 мікро- та 4 ультрамікроелементи. У всіх видах сировини встановили найвищий вміст калію (не менш ніж 2300 мг/кг), що можна пов’язати з певними аспектами дії препаратів із м’яти перцевої. Дополнительного изучения требует довольно распространенное растение – мята перечная (Mentha piperita) семейства губоцветных (Lamiaceae). В дикорастущем состоянии неизвестна, представляет собой гибрид. Терапевтическая активность растения обусловлена комплексом биологически активных веществ, среди которых выделяют макро- и микроэлементы. С целью изучения качественного состава и количественного содержания макро- и микроэлементов в листьях исследовали три образца мяты перечной с помощью атомно-эмиссионной спектрометрии с фотографической регистрацией. Элементный состав всех изучаемых объектов одинаковый: 5 макро-, 15 микро- и 4 ультрамикроэлемента. Во всех видах сырья установили высокое содержание калия (не менее 2300 мг/кг), что можно связать с определенными аспектами действия препаратов из мяты перечной. Our attention has been drawn to the fairly common plant, namely peppermint (Mentha piperita), of Labiatae family (Lamiaceae). This plant is unknown in wild state, it is a hybrid obtained by crossing water mint (Mentha aquatica) with spicate mint (Mentha spicata) or green mint (Mentha viridis). Therapeutic activity of the plant is caused by complex of biologically active substances, macro- and micronutrients are among them. Accumulation of elements in plants depends on the type and plant species, climatic conditions and geographical habitat. Aim. The purpose of work is to study qualitative and quantitative composition of the macro-and micronutrients’ content in leaves of 3 samples of peppermint. Methods. In order to study elemental composition of peppermint leaves we used the method of atomic emission spectrometry with photographic registration. Qualitative and quantitative composition of the elements’ content in leaves of 3 samples of peppermint has been defi ned by atomic emission spectrometry. Conclusion. The elemental composition of the studied objects is the same: at least 5 macro, 15 micro and 4 ultramicroelements have been found. In all kinds of raw materials the highest potassium content (not less than 2300 mg/kg) has been found, this may be associated with certain aspects of peppermint drugs action.
Изучение элементного состава мяты перечной (Mentha piperita)
The study of the elemental composition of peppermint (Mentha piperita)
Keywords: м’ята перцева; листя рослин; мікроелементи; мята перечная; листья растений; микроэлементы; mentha piperita; plant leaves; trace elements